2012
DOI: 10.1371/journal.pone.0044405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Reference Genes in Papaya for Accurate Transcript Normalization under Different Experimental Conditions

Abstract: Real-time reverse transcription PCR (RT-qPCR) is a preferred method for rapid and accurate quantification of gene expression studies. Appropriate application of RT-qPCR requires accurate normalization though the use of reference genes. As no single reference gene is universally suitable for all experiments, thus reference gene(s) validation under different experimental conditions is crucial for RT-qPCR analysis. To date, only a few studies on reference genes have been done in other plants but none in papaya. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
128
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 73 publications
15
128
0
6
Order By: Relevance
“…For Lilium formosanum, Volvox carteri, and Solanum melongena, 18S displays the most stable expression among samples both from different developmental stages and different stress treatments. However, in our study, 18S performed poorly, which was similar to the results obtained in papaya (Zhu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…For Lilium formosanum, Volvox carteri, and Solanum melongena, 18S displays the most stable expression among samples both from different developmental stages and different stress treatments. However, in our study, 18S performed poorly, which was similar to the results obtained in papaya (Zhu et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Results from the three approaches were subsequently analyzed according to Zhu et al (2012). This method gives a comprehensive ranking with the overall results obtained by the three algorithms used, assigning a number to each gene (between 1 to the most stable to 6 to the least stable one) according to their position …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the current study is the first to identify stable reference genes in leaves and roots of creeping bentgrass under different abiotic stresses (salt, drought, heat, and cold) using the combination of GeNorm, NormFinder, BestKeeper, and RefFinder (Andersen et al 2004;Vandesompele et al 2002). The previous study indicated that different reference genes could be determined by three different softwares (GeNorm, NormFinder, and BestKeeper) based on different mathematical methods or parameters (Chen et al 2014;Huang et al 2014;Zhu et al 2012). Therefore, a comprehensive analysis method named RefFinder was used to achieve reliable results based on the data of different softwares.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive rankings of candidate references shown in Table 2 were determined by RefFinder tool (http://www.leonxie.com/referencegene.php) based on different software programs including GeNorm, NormFinder, and BestKeeper (Chen et al 2014;Huang et al 2014;Zhu et al 2012). PP2A, CACS, and GAPDH were identified as the three most stable reference genes in the total samples.…”
Section: Reffinder Analysismentioning
confidence: 99%